ANALISIS KARAKTERISTIK SIFAT FISIK TANAH PADA BERBAGAI PENGGUNAAN LAHAN DI WILAYAH KECAMATAN PUJON - Putri, Devina Ristanti; Sasongko, Purnomo Edi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2023)
[SOIL PHYSICAL PROPERTIES UNDER DIFFERENT LAND USE TYPES IN PUJON DISTRICT, EAST JAWA, INDONESIA ]. Soil quality may be affected by land use types because these may cause alterations in soil physical properties  determining, in turn, a reduction in land productivity. Therefore, this study aimed to evaluate the impact on soil physics of different land use types in an area of Pujon, East Jawa, Indonesia by determining several soil physical indicators.The changes in these indicators were assayed on top soil samples (0-30 cm and 30-60 cm) in three replicates collected with purposive sampling method in Pujon Region under three different landuse types (dry land, garden, and forest). Moreover, assessing field conditions of the three landuse was carried out by survey method and ArcGIS software. Results showed that the three types of land use have a texture of loam, sandy loam, clay loam, and granular structure. Moisture content varied from 17.84% - 22.18%. The range of bulk density was from 0.71 – 1.06 g/cm3 for dry land with slope class 3 and classified as poor status. Specific gravity ranged from 2.58 – 2.65 g/cm3. The total pore space ranged from 59.23% – 72.80%. The permeability ranged from 3.92 – 14.55 cm/hour and categorized as a bad to good status.